Simplify the equation if possible. Then graph the equation using the \( x \)-intercept and the \( y \)-interce \( 2 x-y=-2 \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To simplify the equation \( 2x - y = -2 \), we can rearrange it to solve for \( y \): \[ y = 2x + 2. \] This equation is now in slope-intercept form ( \( y = mx + b \) ), where the slope \( m \) is 2 and the y-intercept \( b \) is 2. Now, let's find the intercepts. - For the \( x \)-intercept, set \( y = 0 \): \[ 0 = 2x + 2 \implies 2x = -2 \implies x = -1. \] - For the \( y \)-intercept, set \( x = 0 \): \[ y = 2(0) + 2 = 2. \] So the intercepts are \( (-1, 0) \) and \( (0, 2) \). To graph this equation, plot the points \( (-1, 0) \) and \( (0, 2) \), and draw a straight line through them. That line represents the equation \( 2x - y = -2 \).